1989
DOI: 10.1136/bjo.73.10.816
|View full text |Cite
|
Sign up to set email alerts
|

Association between keratoconus and atopy.

Abstract: SUMMARY Sixty-seven patients with keratoconus were classified according to atopic status. Keratoconus patients with and without atopy did not differ significantly with regard to sex, age of onset, or rate of keratoplasty, but patients with very high IgE levels were more prone to graft rejection. Atopy was less common in patients with unilateral keratoconus, and keratoconus occurred more frequently on the side of the dominant hand. There was a significantly lower frequency of HLA B7 in the keratoconus group tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
9

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 11 publications
2
81
0
9
Order By: Relevance
“…31,35 Conversely, reports of monozygotic twins who were discordant for keratoconus have been published. 33,46,47 This can be explained by epigenic, stochastic and environmental factors. In cases in which there was KC discordance in identical twins, eye rubbing and hormonal influences were suggested as possible environmental factors involved in the etiology of KC.…”
Section: Twin Studiesmentioning
confidence: 99%
“…31,35 Conversely, reports of monozygotic twins who were discordant for keratoconus have been published. 33,46,47 This can be explained by epigenic, stochastic and environmental factors. In cases in which there was KC discordance in identical twins, eye rubbing and hormonal influences were suggested as possible environmental factors involved in the etiology of KC.…”
Section: Twin Studiesmentioning
confidence: 99%
“…9,10 However, as many of the patients with ocular allergic diseases rub their eyes excessively, it remained unclear whether atopy itself or eye rubbing was the factor related to keratoconus. Harrison et al 6 found that in atopic keratoconus patients, the disease occurred more frequently on the side of the dominant hand. More recently, in 2000, Bawazeer et al 11 published their results of a case-control study, which showed in the univariate associations that there was an association between keratoconus and atopy, as well as eye rubbing and family history of keratoconus.…”
Section: Introductionmentioning
confidence: 99%
“…Association between atopy and keratoconus has been identified for more than 50 years, but multiple studies have shown conflicting results. [4][5][6][7][8] Higher levels of serum immunoglobulin E was found in 59% of keratoconus patients in studies performed around 30 years ago. 9,10 However, as many of the patients with ocular allergic diseases rub their eyes excessively, it remained unclear whether atopy itself or eye rubbing was the factor related to keratoconus.…”
Section: Introductionmentioning
confidence: 99%
“…A apoptose de ceratócitos, que ocorre com freqüência muito maior em córneas com ceratocone do que em córneas normais consiste em um reforço à possível influência genética sobre a doença (44) . O antígeno HLA-B7 é sugerido como marcador de proteção (45) . Ihalainen (1986) realizou a tipagem de antígenos HLA-A, -B e -C em famílias com múltiplos casos de ceratocone (46) .…”
Section: Ceratocone De Início Na Juventudeunclassified